Sleep characteristics and cognitive impairment in the general population: The HypnoLaus study. (31st January 2017) - Haba-Rubio, José; Marti-Soler, Helena; Tobback, Nadia; Andries, Daniela; Marques-Vidal, Pedro; Waeber, Gérard; Vollenweider, Peter; von Gunten, Armin; Preisig, Martin; Castelao, Enrique; Tafti, Mehdi; Heinzer, Raphaël; et al.
Abstract : Objective: To assess the association between sleep structure and cognitive impairment in the general population. Methods: Data stemmed from 580 participants aged >65 years of the population-based CoLaus/PsyCoLaus study (Lausanne, Switzerland) who underwent complete sleep evaluation (HypnoLaus). Evaluations included demographic characteristics, personal and treatment history, sleep complaints and habits (using validated questionnaires), and a complete polysomnography at home. Cognitive function was evaluated using a comprehensive neuropsychological test battery and a questionnaire on the participant's everyday activities. Participants with cognitive impairment (global Clinical Dementia Rating [CDR] scale score > 0) were compared with participants with no cognitive impairment (global CDR score = 0). Results: The 291 participants with a CDR score > 0 (72.5 ± 4.6 years), compared to the 289 controls with CDR = 0 (72.1 ± 4.6 years), had significantly more light (stage N1) and less deep (stage N3) and REM sleep, as well as lower sleep efficiency, higher intrasleep wake, and higher sleepiness scores (all p < 0.05). Sleep-disordered breathing was more severe in participants with cognitive impairment with an apnea/hypopnea index (AHI) of 18.0 (7.8–35.5)/h (p50 [p25–p75]) (vs 12.9 [7.2–24.5]/h, p < 0.001), and higher oxygen desaturation index (ODI). In the multivariate analysis after adjustments for confounding variables, the AHI and the ODI ≥4% and ≥6% were independently associated with cognitive impairment. Conclusions: Participants aged >65 years with cognitive impairment have higher sleepiness scores and a more disrupted sleep. This seems to be related to the occurrence of sleep-disordered breathing and the associated intermittent hypoxia.